PERBEDAAN KONSENTRASI PEWARNA ALAMI KULIT BUAH NAGA (Hylocereus polyrhizus) TERHADAP WARNA TERASI UDANG REBON (Acetes sp.) - Permatasari, Amelia Ayu; Sumardianto, Sumardianto; Rianingsih, Laras (Jurnal Teknologi Hasil Pertanian, 2018)
Shrimp paste is one of fermented product that use either shrimp (Acetes sp.), or fish, or both of them as raw materials. The use of synthetic dyes on shrimp paste is still often done. This is dangerous because it can give bad effect to the health of consumers. Therefore, it is necessary to use natural dyes instead of synthetic dyes. One of natural dyes that can be used is peel of dragon fruit (Hylocereus polyrhizus). Peel of dragon fruit has anthocyanin pigment that can give red color. The aimed of this research was knowing the effect of adding peel of dragon fruit extract (30%; 35%; 40%) to the color of shrimp paste. The treatments in this study were the addition of different concentrations of peel of dragon fruit extract at third grinding shrimp paste in triplicate. The experimental design used was Completely Randomized Design. The parameters observed include moisture content, salt content, protein content, pH, color, and sensory. Parametric data analyzed by Analysis of Variance (ANOVA) and further test by Honestly Significant Difference (HSD) test if these any differences between samples. Non-parametric data analyzed by Kruskal-Wallis and further test by Mann Whitney. The research’s result showed that processing shrimp paste with different peel of dragon fruit extract concentrations gave significant effect (P<5%) on moisture content, salt content, pH, and color. Moisture content values was ranged from 35,0741,01% and salt content values was ranged from 6,35-7,05%. pH values was ranged from 6,40-7,20. Shrimp paste with peel of dragon fruit extract 40% had more red color and improve the appearance of shrimp paste.